Zinc finger protein ZPR9 functions as an activator of AMPK-related serine/threonine kinase MPK38/MELK involved in ASK1/TGF-β/p53 signaling pathways - Seong, Hyun-A (Sci Rep, 2017)
Murine protein serine-threonine kinase 38 (MPK38), an AMP‐activated protein kinase (AMPK)-related kinase, has been implicated in the induction of apoptosis signal-regulating kinase 1 (ASK1)-, transforming growth factor-β (TGF‐β)-, and p53-mediated activity involved in metabolic homeostasis. Here, zinc finger protein ZPR9 was found to be an activator of MPK38. The association of MPK38 and ZPR9 was mediated by cysteine residues present in each of these two proteins, Cys(269) and Cys(286) of MPK38 and Cys(305) and Cys(308) of ZPR9. MPK38 phosphorylated ZPR9 at Thr(252). Wild‐type ZPR9, but not the ZPR9 mutant T252A, enhanced ASK1, TGF‐β, and p53 function by stabilizing MPK38. The requirement of ZPR9 Thr(252) phosphorylation was validated using CRISPR/Cas9-mediated ZPR9 (T252A) knockin cell lines. The knockdown of endogenous ZPR9 showed an opposite trend, resulting in the inhibition of MPK38‐dependent ASK1, TGF‐β, and p53 function. This effect was also demonstrated in mouse embryonic fibroblast (MEF) cells that were haploinsufficient (+/−) for ZPR9, NIH 3T3 cells with inducible knockdown of ZPR9, and CRISPR/Cas9-mediated ZPR9 knockout cells. Furthermore, high-fat diet (HFD)-fed mice displayed reduced MPK38 kinase activity and ZPR9 expression compared to that in mice on control chow, suggesting that ZPR9 acts as a physiological activator of MPK38 that may participate in obesity.